Legal Consequences of a Morally Defective (Fasiq) Instrumental Witness on the Execution of Sharia Financing Collateral: A Comparative Approach - Nurluna Siti Syarah; Agung Iriantoro; Ricca Anggraeni (SIGn Jurnal Hukum, 2026)
The disparity in the position of the instrumental witness in the creation of Sharia financing deeds originates from the collision between the formal rationality of positive law and the ontological values of Islamic law. Notarial practice tends to be oriented towards fulfilling administrative requirements without burdening the witness with material liability, whereas Islamic law absolutely demands the ‘adalah (highest moral integrity) qualification. This research aims to examine the dogmatic comparison of the instrumental witness position in both legal regimes and analyze its implications on the validity of the contract and the executory force of the Mortgage Right collateral. This research is a normative juridical study that utilizes the statutory, conceptual, and comparative approaches. The research results indicate that the use of a witness with defective moral integrity (fasiq) degrades the evidentiary power of the deed into a private deed under positive law and renders the contract status fasid (attributively defective making it voidable) under Islamic law. The dogmatic consequences of this double defect in the principal agreement are fatal for the accessory instrument. The Mortgage Right guarantee certificate automatically loses its theological legitimacy foundation, thus becoming paralyzed in executing parate executie (direct execution clause) at the Religious Court. In conclusion, disregard for witness integrity undermines the entire legal protection framework for the creditor. Therefore, integrating the fiqh muamalah (Islamic commercial jurisprudence) into notarial technical guidelines is necessary to prevent administrative malpractice and safeguard the validity of Sharia economic transactions.